Implementasi Nilai-Nilai Pendidikan Islam Pada Remaja Islam Masjid - Riswandy Riswandy (At-Ta'lim : Media Informasi Pendidikan Islam, 2023)
Absract: Implementation Of Islamic Values in Mosque YouthRisma is one of the important tools that needs to be activated in the community in providing Islamic Religious education to be implemented both in academia and in society both through recitation, Tausyah, dhikr and other activities related to Islamic Religious values. The purpose of this study was to explore the values of Islamic education carried out by the Youth of the Al Muhajirin Mosque, Talang Benih Curup Village. This research is a field research, the type of research conducted is qualitative research with a qualitative descriptive approach. The subjects in this study were mosque officials, the community and several members of Risma Al-Muhajirin. Relevant data collection techniques used in this study are observation, interviews, and documentation. While the technique for data analysis is by means of data reduction, data presentation, and drawing conclusions. The data collection technique was then carried out by the actor checking with the triangulation technique and then reducing the data and then drawing a conclusion which the researcher then claimed was a research finding. The results of the study concluded that the implementation of the values of Islamic education itself includes the formation of character, worship and morals and is able to shape the behavior of adolescents so that they do not carry out negative activities such as crimes, stealing and promiscuity which have occurred a lot among adolescents and can increase positive behavior. With the implementation of the values of Islamic education that are taught to youth in this mosque, it greatly influences the youth of the mosque itself in forming mosque youth which encourages youth towards positive activities which can later become a generation of youth who can be a good example, especially in society.Abstrak: Implementasi Nilai-Nilai Pendidikan Islam pada Remaja Islam MasjidRisma merupakan salah satu sarana penting yang perlu diaktifkan di lingkungan masyarakat dalam memberikan pendidikan Agama Islam untuk diimplementasikan baik di akademik maupun di masyarakat baik melalui pengajian, Tausyah, dzikir dan kegiatan lainnya yang berhubungan dengan nilai-nilai Agama Islam. Adapun tujuan penelitian ini adalah untuk menggali nilai-nilai pendidikan Islam yang dilaksanakan oleh Remaja Masjid Al Muhajirin Kelurahan Talang Benih Curup. Penelitian ini merupakan penelitian lapangan, jenis penelitian yang dilakukan adalah penelitian kualitatif dengan pendekatan deskriptif kualitatif. Subjek dalam penelitian ini adalah pengurus Masjid, masyarakat dan beberapa anggota Risma Al-Muhajirin. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Sedangkan teknik untuk analisis datanya yaitu dengan cara reduksi data, penyajian data, dan penarikan kesimpulan. Teknik pengumpulan data kemudian pelaku melakukan krocek dengan Teknik triangulasi dan kemudian direduksi data tersebut baru diambil sebuah kesimpulan yang kemudian peneliti claim sebagai temuan penelitian. Di risma Al-Muhajirin terdapat beberapa kegiatan yang rutin dilaksanakan seperti: yasinan, pengajian, muhadaroh, Khutbah Jum’at, membantu kegiatan PHBI yang tentunta kegiatan tersebut dapat menghidupkan pendidikan Islam di Masyarakat. Hasil penelitian disimpulkan bahwa dengan adanya kegiatan tersebut mampu membentuk perilaku remaja agar tidak melakukan kegiatan yang melanggar norma-norma yang dilarang seperti kejahatan-kejahatan, mencuri dan pergaulan bebas yang sudah banyak terjadi dikalangan remaja serta dapat meningkatkan perilaku positif.